FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN: STUDI PADA INDEKS LQ45 - Ervina Gunawan; Karina Harjanto (Universitas Kristen Krida Wacana, 2021)
The objective of this research was to examine the effect of liquidity, good corporate governance, firm size, and leverage towards company performance. The object in this research was companies listed in LQ45 index for period 2016 until 2018. The sample was selected by using purposive sampling method and data used in this study is a secondary data. In total, there were 14 companies that fulfill the requirements set by the researcher. This research was analyzed by using multiple regression method. The result of this research were that liquidity and firm size had no positive effect on company performance, leverage had negative but not significant effect on company performance, and GCG had positive and significant effect on company performance. Keywords: Company’s Performance, Firm Size, Good Corporate Governance, Leverage, Liquidity.